Measurement and analysis of rally car dynamics at high attitude angles - Croft-White, Michael (Cranfield University, 2006)
This research aims to investigate the nature of high β-angle cornering as seen in rallying and in particular the World Rally Championship. This is achieved through a combination of sensor development, on-car measurement and vehicle dynamic simulation. Through the development of novel β-angle measurement technology it has become possible to measure and study vehicle attitude dynamics on loose gravel surfaces. Using this sensor, an understanding of how a rally driver uses the dynamics of the vehicle and surface to maximise performance has been obtained. By combining the new data stream with accepted vehicle dynamic theory, the tyres have been considered and general trends in gravel tyre performance unveiled. Through feedback, these trends have been implemented as a means of tuning a dynamic model to improve realism and permit an analysis of cornering trends in rally cars. Active control systems have been considered that could implement more sophisticated algorithms based on this understanding and potentially use the new sensor information as an input signal. A case study which explores such a possibility is included.